The Degree of Practicing of Public-School Principals to Technological Leadership in Aqaba Governorate in Light of the Corona Pandemic from Teachers’ Point of View for the Academic year 2020-2021 - Al-Quabe'h, Wafa' Abdulrahim (Journal of Educational and Psychological Sciences, 2022)
The study aimed to reveal the degree to which public school principals practice technological skills from teachers’ point of view in the Aqaba Governorate in light of the Corona pandemic. The descriptive survey method was adopted to achieve the objectives of the study where a questionnaire was developed that included (35) paragraphs, the study sample takes by simple random method from the study population, and it consisted of (200) male and female teachers. The statistical package for the social sciences (SPSS) was used to analyze the data. The study results concluded that the degree of technological leadership practice among principals of primary schools in light of the Corona pandemic from the teachers’ point of view came to a high degree. The study results found that there are statistically significant differences at the level of significance (α ≥ 0.05) in the impact of the gender differences tend in favor of females with an arithmetic mean higher than the arithmetic mean for males. Whereas the females see the administration’s application of technological leadership to provide the student’s right to learn despite the challenges that the Kingdom is experiencing as a result of the Corona pandemic in the educational sector and other sectors). The arithmetic averages for the level of application of government school principals to technological leadership ranged between (3.70- 4.60 out 5), this indicates the high level of application. Paragraph No. (10) came in the first place, which states, "The principal uses the presentation program during school meetings, " with an arithmetic mean of (4.60). While Paragraph No. (28) states, "The principal makes supervisory visits to teachers during their training of students in remote meetings, "on the last rank, with a mean of (3.70). The study recommended increasing the education and training of administrative leaders on applying modern technological concepts and practices in management.